The association of liver enzymes with diabetes mellitus risk in different obesity subgroups: A population-based study - Zheng, Dinghao; Zhang, Xiaoyun; You, Lili; Li, Feng; Lin, Diaozhu; Sun, Kan; Ren, Meng; Yan, Li; Wang, Wei (Frontiers in Endocrinology, 2022)
Backgroud Numerous observational studies have showed that liver enzymes correlated with diabetes mellitus (DM) risk significantly, but limited study showed whether different obesity subgroups present the same correlation. Our object was to evaluate the association of liver enzymes with DM risk in different obesity subgroups based on a middle-aged Chinese population. Methods We conducted a population-based cross-sectional study, surveyed 9,916 people aged 40 years above. Two-slope linear regression model was used to analyze the cut-off points of obesity in DM risk. Restricted cubic splines were used to analyze the correlation between liver enzymes and DM risk in different obesity categories. The odds ratios and 95% confidence intervals (CIs) were calculated by logistic regression model. Results The cut-off points of BMI and waist circumference are 30.55kg/m2 and 98.99 cm for DM risk, respectively. The serum GGT concentration was positive correlated with the DM risk in the waist circumference < 98.99cm (OR=1.04, 95% CI (1.03-1.05)), BMI <30.55kg/m2 (OR=1.04, 95% CI (1.03-1.05)) and BMI >=30.55kg/m2 subgroup (OR=1.18, 95% CI (1.04-1.39)), not in the waist circumference >= 98.99cm subgroup. Alanine aminotransferase (ALT) and Aspartate aminotransferase (AST) concentrations have no significance correlation with the risk of diabetes in all groups. Conclusion The results showed that serum GGT concentration was correlated with DM risk not AST or ALT in middle-aged population. But the correlation disappeared when waist circumference was over 98.99cm. Serum GGT concentration had limited value for DM risk in waist circumference over 98.99cm population.